The Role of Acoustic Phonons in the Formation of Thermophysical Properties of PbI2 Nanofilms - Крамар, Валерій Максимович (Journal of Thermoelectricity, 2025)
Based on the dispersion dependences of acousticphonon frequencies in hexagonal quasitwo-dimensional nanostructures, previously obtained by us in the elastic continuum approximation, the heat capacity, entropy, free energy (Helmholtz), and thermal diffusion coefficient of nanometer-thick planar structures (nanofilms) of lead diiodide were calculated. The dependence of these quantities on the nanofilm thickness and temperature, as well as the role of different branches of the phonon spectrum in the formation of the thermophysical properties of such structures, was investigated. The results of calculating the heat capacity, entropy, free energy, and thermal diffusion coefficient of lead diiodide nanofilms indicate that all of them depend on the nanofilm thickness. This dependence is especially pronounced in ultrathin (up to 8 PbI2 layered packages thick) nanofilms. The absolute values of all these quantities increase with a rise in temperature in nanofilms of any thickness. In the low-temperature range, the rate of increase is slower for thinner nanofilms. At temperatures above the Debye temperature, the growth of heat capacity and entropy slows down; the C(T) dependence practically disappears, and the rate of growth of entropy S decreases the more,the greater the nanofilm thickness. Due to the difference in the rates of change of entropy in nanofilms of different thickness, inthe region T ~ 400 K, the inversion of the S(T) dependence occurs – the entropy acquires values that are the greater, the thinner the nanofilm. The rate of change of the free energy upon reaching the Debye temperature acquires its greatest value, so that with a subsequent rise in temperature, the free energy changes linearly at a rate whose value is practically independent of the nanofilm thickness. It has been shown that phonons with transverse polarizations – displacement and bending – have the greatest influence on thermophysical processes controlled by heat capacity, entropy, and free energy. Thermal diffusion, like thermal conductivity, is determined primarily by longitudinal – dilatation phonons.
Keywords: nanostructures, nanofilm, lead diodide, acoustic phonons, thermophysical properties, heat capacity, thermal diffusion, free energy, entropy